2017
DOI: 10.1049/oap-cired.2017.1248
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of electrical distribution grid sizing considering self-consumption of local renewable production

Abstract: In the last decades, renewable energy sources have been increasing their shares in the world energy market. In addition to the ecological benefits, this trend can have adjunct benefits, for example for distribution system operators: a gain in their grid sizing. Indeed, installation of decentralized production, when used in a selfconsumption approach, can lead to reduction of the consumption peaks. This work is willing to quantify what grid sizing reduction a distribution system operator can expect, knowing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…The wind was one of the potential energy sources in that experiment. Researchers often study the effects of combining solar PV and wind energy production on a microgrid operation [12,13]. Increasing self-consumption stabilises load peaks and decreases costs on the electrical energy purchase [14].…”
Section: Overview Of Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…The wind was one of the potential energy sources in that experiment. Researchers often study the effects of combining solar PV and wind energy production on a microgrid operation [12,13]. Increasing self-consumption stabilises load peaks and decreases costs on the electrical energy purchase [14].…”
Section: Overview Of Literaturementioning
confidence: 99%
“…In Spain, different energy generation systems based on solar PV are competitive and profitable without subsidies in self-consumption schemes [28]. In fact, the setting up of distributed generation, when exploited in a self-sufficiency manner, may decrease the utilisation peaks [29]. Scientists and experts demonstrated that this kind of arrangement might enhance a microgrid's resilience and improve the level of self-consumption whilst decreasing the grid loads, which means being cost-effective up to 60% of self-consumption [30].…”
Section: Overview Of Literaturementioning
confidence: 99%
“…This model is particularly useful to simulated diffuse production before the calibration of the electric load curve simulator. It is also of a great interest to test different local renewable production penetration rates and its influence on electrical grid sizing [3].…”
Section: Production Load Curve Simulationmentioning
confidence: 99%
“…Households require power supplies from the largest possible number of renewable sources to reduce payoff times [2,30]. Increasing self-consumption not only levels load peaks [31] but also decreases costs on the electrical energy import to an economically feasible point of 60% self-consumption level [32].…”
Section: Introductionmentioning
confidence: 99%